The sensitive Amnesia Light and Brief Assessment (ALBA) is a valid 3-min test of 4 tasks indicative of mild cognitive deficits - Bartos, A; Diondet, S (Neurologia, 2025)
BACKGROUND AND PURPOSE: We report the development and validation of a unique, easily administered, but cognitively demanding 3-min test that does not require aids and can detect mild cognitive deficits (MCD). METHODS: The innovative Amnesia Light and Brief Assessment (ALBA) consists of 4 tasks: encoding the 6-word sentence "Indian summer brings first morning frost," sequential demonstration of 6 gestures and their immediate recall, and final recall of the original sentence. The memory ALBA score is the sum of all correctly recalled sentence words and gestures. The ALBA was performed in 590 persons older than 50 years, including 60 individuals who completed a neuropsychological battery, equally divided into patients with MCD (Montreal Cognitive Assessment [MoCA] score of 21±3 points) and matched cognitively normal (CN) individuals (MoCA of 27±2). RESULTS: Compared to CN individuals, the patients with MCD recalled fewer correct sentence words (median, 5 vs 2) and gestures (4 vs 3), and had lower memory ALBA scores (10 vs 6) (all comparisons, P<.00001). The cut-off point for the memory ALBA score was ≤8, with 90% sensitivity, 77% specificity, and an AUC of 0.90. Memory ALBA score correlated significantly with all neuropsychological tests except the Digit Span forward. The ALBA was minimally associated with education and age in the normative sample. CONCLUSIONS: The novel and efficient ALBA test was confirmed to have high discriminant and convergent validity, even in patients with mild cognitive deficits. The ALBA is an ultra-brief and universal cognitive test suitable for assessing cognitive impairment, dementia, and other conditions. It can easily be adapted to other cultures and administered under various conditions and settings in clinical practice and research.
Keywords: Dementia; ALBA; Amnesia; Female; Cognitive Dysfunction; Neuropsychological Tests; rozpomínání; ženské pohlaví; neuropsychologické testy; lidé; Mental Recall; Sensitivity and Specificity; senzitivita a specificita; Amnesia Light and Brief Assessment; Cognitive impairment; amnézie; Male; Aged; kognitivní dysfunkce; lidé středního věku; Test cognitivo; Screening; senioři; mužské pohlaví; Demencia; Middle Aged; Cognitive test; Deterioro cognitivo; Humans